BUILDING AN EDUCATIONAL PROGRAM BASED ON METACOGNITIVE THINKING STRATEGIES TO DEVELOP LINGUISTIC WEALTH FOR PREP STUDENTS IN LITERATURE AND TEXT - Oleiwi, Marwa Adnan; Al-jibury, Arif Hatem; hasan, Thaer Sameer (International Journal of Psychosocial Rehabilitation, 2020)
The current study aimed at (building a proposed educational program based on the strategies of epistemological thinking to develop linguistic wealth for prep students in literature and text).The questionnaire included a set of strategies that fall within metacognitive thinking of literature and texts for the fifth grade scientific, included (15) strategies that fall within metacognitive theory, and (5) strategies were chosen that fall within metacognitive thinking, and are appropriate for teaching literature and texts in middle School.The researcher used a square (chi) statistical method to know the extent of the experts' agreement on the chosen behavioral goals and the teaching plans, and accordingly the researcher presented a set of recommendations, including experimenting with the proposed program to learn about its effectiveness in developing linguistic wealth in the literature and texts subject for fifth-grade students.